Perbandingan Pemberian Buah Naga Dan Buah Bit Terhadap Kadar Hb Remaja Putri Di Pondok Pesantren Modern Ar-Rahman Kecamatan Tanjung Lubuk Kabupaten Oki Palembang - Ambar Yanti; Titin Eka Sugiatini (Jurnal Keperawatan Muhammadiyah, 2023)
Background: The prevalence of anemia in young women is still high. In 2022, out of 55 students, 24 students (48%) were found to have anemia. As an effort to prevent this, the Islamic Boarding School is working with the Health Center to carry out a program of administering 1 fe tablet once a week. Prevention of anemia in young women apart from Fe supplements can also be done by consuming foods that contain iron, such as dragon fruit and beets. Research Objectives: To determine the ratio of giving dragon fruit and beetroot to Hb levels of female adolescents at the Ar-Rahman Modern Islamic Boarding School, Tanjung Lubuk District, Oki Regency, Palembang. Research Method: quasy experimental design with pretest-posttest design with control group design. The sample consisted of 24 female adolescents who experienced anemia in January-February 2023 using a purposive sampling technique. The intervention was given 250g once a day for 14 days. Bivariate analysis used paired simple t test and independent t test. Results: The results of the univariate study showed that the Hb level of female adolescents before administration of dragon fruit averaged = 10.225 gr/dl and after administration of dragon fruit averaged = 10.650 gr/dl. The Hb level of female adolescents before giving beets averaged = 10.342 gr/dl and after giving beets the average = 11.017 gr/dl. The results of the bivariate study obtained a p value = 0.000. Conclusions and Suggestions: There are differences in the effect of dragon fruit and beetroot on female adolescent Hb levels. Young women are expected to be diligent in consuming foods that contain iron, one of which is beetroot and lemon juice and be obedient in consuming Fe tablets in order to increase Hb levels in the blood of young women.